Basic values as a motivational framework relating individual values with acculturation strategies among Arab immigrants and refugees across different settlement contexts - Abu-Rayya, Hisham M.; Berry, John W.; Lepshokova, Zarina; Alnunu, Momin; Grigoryev, Dmitry (Frontiers in Psychology, 2023)
There is a lack of systematic acculturation research on the motivations underpinning the behavior of migrants, which could explain how they acculturate and adapt to their new country of residence. This paper applies the Schwartz Theory of Basic Individual Values to explain the link between values and acculturation strategies among Arab immigrant and refugee groups across different settlement contexts. The results of Study 1 (Arab immigrants; N = 456) showed, as hypothesized, positive links between strategies and values: the integration strategy with conservation, social focus, self-protection, and self-transcendence values; assimilation with openness to change, personal focus, and growth values; and separation with conservation, social focus, and self-protection. These findings were generally repeated in Study 2 (Syrian refugees; N = 415) except that integration was not associated with self-transcendence and that assimilation was positively linked to self-enhancement instead of openness to change. Our analyses indicated that acculturation preferences are mainly related to motivational values, rather than to different settlement contexts in both samples; however assimilation seems to be more associated to context than values among the refugee sample. Implications of the findings to the acculturation literature are discussed.